Aversion of European Starlings (Sturnus vulgaris) to Garlic Oil Treated Granules: Garlic Oil as an Avian Repellent. Garlic Oil Analysis by Nuclear Magnetic Resonance Spectroscopy - Hile, Arla G; Shan, Zhixing; Zhang, Shao-Zhong; Block, Eric (Journal of agricultural and food chemistry, 2004)
European starlings significantly reduced their consumption of a food mixture that was 50% food-grade garlic oil (GO)-impregnated granules, even after overnight food deprivation, as demonstrated by “one-choice” (“no-choice”) tests. Food consumption during 3 h following overnight food deprivation was reduced by 61−65% compared to controls. By testing the same subjects with 25, 10, and 1% mixtures of granules in feed, it was shown that commercial GO granules were repellent to birds in lower concentrations, with more than a 50% decrease in feeding for birds presented with a 10% mixture of commercial GO granules in food and a 17% decrease for the 1% treatment. Products containing GO show considerable promise as inexpensive, environmentally benign, nonlethal bird repellents. In comparing various GO preparations used in this work, nuclear magnetic resonance (NMR) spectroscopic methods prove to be particularly useful for rapid quantitation of major and minor components without requiring fractionation or isolation procedures, which could adversely effect the less stable components. Keywords: Garlic oil; Allium sativum; European starlings; Sturnus vulgaris; avian repellents; NMR methods